Harold Otis "Gabe" Bicknell - Peter Stackpole:::Creator::::::::::::
Harold Otis 'Gabe' Bicknell, the model for 'Mack' from Cannery Row. The 'Palace Flop House and Grill' is in the background. RESTRICTED USE. Original is in the safe.